Parental Stress, Depression, Anxiety, and Participation in Neonatal Care in a Referral Brazilian NICU over Different Phases of the COVID-19 Pandemic - Dafne Barcala Gomez; Emanuelle Pessa Valente; Paolo Dalena; Ilaria Mariani; Suely Arruda Vidal; Maria Júlia Gonçalves Mello; Geyse Lima; Juliana Barradas Souza; Waldemar Brandão Neto; Vanessa Tenório Rodrigues; Bruna Malta Castro; Maria Luísa Pessoa; et al. (Children)
Background/Objectives: During the COVID-19 pandemic, neonatal care units had to change protocols, and little is known about its impact on parents’ mental health. This study aimed to evaluate parental stress, depression, anxiety, and participation in neonatal care in a Brazilian neonatal intensive care unit (NICU) and observe changes over two different periods of the COVID-19 pandemic. Methods: Cross-sectional study comparing stress, depression, anxiety, and participation in neonatal care levels between two time periods: T1, high COVID-19 incidence (May 2020 to July 2020 and March 2021 to June 2021) and T2, low COVID-19 incidence (August 2020 to February 2021 and July 2021 to December 2021). High COVID-19 incidence was considered more than 40 confirmed COVID-19-related deaths/day. Validate tools used were the Parental Stressor Scale in NICU (PSS:NICU); the Edinburgh Postnatal Depression Scale (EPDS); the Edinburgh Postnatal Depression Scale-Anxiety subscale (EPDS-A); the State-Trait Anxiety Inventory (STAI); and the Index of Parental Participation (IPP). Stress level was pre-defined as the primary outcome. Results: 106 parents (98 mothers, 8 fathers) and 111 newborns were included. Overall, 51.9% of parents had a PSS:NICU score ≥ 3 (relevant stress level), 28.3% had an EPDS-A ≥ 6 (indicating anxiety), and 33.0% had an EPDS > 13 (indicating depression). At least one condition was present in 69 (65%) parents, while the three conditions were simultaneously observed in 17 (16%) parents. No significant differences were observed in the frequencies of stress, depression, or anxiety between the two periods. However, median stress occurrence level (SOL) was higher in T1 when compared to T2 (3.24 vs. 2.68; p = 0.02), mainly due to “Parental role alteration” (3.80 vs. 3.17; p = 0.046). The level of parental participation was not different between the two time periods (p = 0.23). Correlations between stress and both depression and anxiety scores were weak. Parental participation was not significantly correlated to other scores. Conclusions: Elevated levels of stress, depression, and anxiety were observed among NICU parents during both high and low COVID-19 incidence periods. High COVID-19 incidence seems to have particularly influenced stress levels related to parental role alteration. These findings highlight the importance of regularly assessing parental mental health in NICU settings.